Multimodal Optical Diagnostics of the Microhaemodynamics in Upper and Lower Limbs - Zherebtsova, Angelina I.; Dremin, Viktor V.; Makovik, Irina N.; Zherebtsov, Evgeny A.; Dunaev, Andrey V.; Goltsov, Alexey; Sokolovski, Sergei G.; Rafailov, Edik U. (Frontiers in Physiology, 2019)
The introduction of optical non-invasive diagnostic methods into clinical practice can substantially advance in the detection of early microcirculatory disorders in patients with different diseases. This paper is devoted to the development and application of the optical non-invasive diagnostic methods for the detection and evaluation of the severity of microcirculatory and metabolic disorders in rheumatic diseases and diabetes mellitus. The proposed methods include the joint use of laser Doppler flowmetry, absorption spectroscopy and fluorescence spectroscopy in combination with functional tests. This technique showed the high diagnostic importance for the detection of disturbances in peripheral microhaemodynamics. These methods have been successfully tested as additional diagnostic techniques in the field of rheumatology and endocrinology. The sensitivity and specificity of the proposed diagnostic procedures have been evaluated.